Construction Dispute Council as an Alternative Dispute Settlement - Yudistira; Serlika Aprita (Universitas PGRI Madiun, 2026)
The process settling of the different perceptions that lead to dispute is very disruptive to the construction activities. Thus the election of dispute resolution must be observed specifically to obtain maximum results. Dispute council and arbitration council are the choice where disagreement that lead dispute must be resolved. Settlement prioritizes values that uphold good relationships, legal certainty and certainty of project sustainability. The assessment between the owner and the contractor is different, besides they prioritize the legal certainty of a dispute, evidently they have their own respective interests, the owner priority is the sustainability of the project to be achieved amid a dispute, in order to keep the business opportunity in the next project. This can be well accommodated by the dispute council by referring to the Fidic Conditions of Contracts. With a sample of 100 respondents in which 47% of Owners and Consultants, 53% of Contractors, they tend to prefer the Dispute Council as a way to resolve construction disputes. The result is 53.7% of the owner and the contractor chooses the dispute councils by prioritizing legal certainty, the sustainability of the project and good relations, while the remaining 29.6% chose Arbitration.